Poor Households' Productive Investments of Cash Transfers : Quasi-Experimental Evidence from Niger - Stoeffler, Quentin; Mills, Bradford; Premand, Patrick (World Bank, Washington, DC, 2016)
Cash transfer programs have spread rapidly as an instrument to raise household consumption and reduce poverty. Questions remain about the sustainability of cash transfer impacts in low-income settings such as Sub-Saharan Africa and, in particular, on whether cash transfers can foster productive investments in addition to raising immediate consumption among the very poor. This paper presents evidence that a cash transfer project in rural Niger induced investments in assets and productive activities that were sustained among the very poor 18 months after project completion. Results show lasting increases in livestock assets and participation in saving groups (tontines). Cash transfers also contributed to improved agricultural productivity, but no effects in terms of diversification of other household enterprises are found. Productive asset gains are, notably, largest among the poorest of the poor, suggesting that small regular cash transfers combined with enhanced saving mechanisms can relax constraints to asset accumulation among the extreme poor.